PELATIHAN PEMBUATAN PUPUK ORGANIK CAIR LONTAR (PocLon) BAGI JEMAAT GEREJA GMIT IMANUEL OEPUNU, KABUPATEN KUPANG - Solle, Hartini Realista Lydia; Manafe, Mesri Welhelmina Nisriani; Nitsae, Merpiseldin; Medah, Andreas Isakh; Mamulak, Yulita Iryani (Universitas Mataram, 2024)
East Nusa Tenggara is the provinces that has a vast plain and is classified as a dry area, this can be proven by various types of plants that can survive in dry areas. One of the plants is Lontar (Borassus flabelifer L.). Lontar is a tropical plant that has many benefits and high economic value. Objective: To improve the ability of partners through eco-green based empowerment that is economically and socially independent by utilising lontar waste as Liquid Organic Fertiliser (LOF), technology application and Human Resources (HR) management. Activity method: The method used is two methods: training conducted involving partners consisting of church fathers in the training process the team also delivered material related to Lontar and the Benefits of Organic Fertilisers and PKM team mentoring was carried out for approximately 8 months. Activity results: The activity was carried out in September 2023 at the Imanuel Oepunu GMIT Church Building. Most people in kupang district use lontar to take lontar sap which is fermented into tuak/laru, lontar fruit is also usually used as animal feed There are 3 groups where each group produces approximately 10 litres of ready-to-use PocLon. In the mentoring process, the Poclon products that have been obtained are applied to crops Conclusion: GMIT Imanuel Oepunu was able to conduct training in making PocLon properly and correctly and was able to work together in the assistance provided by the team. Partners were very enthusiastic in practicing making Poclon and discussing with the team so that the activity was very interactive.